Knowledge, attitudes, barriers and uptake rate of influenza virus vaccine among adults with chronic diseases in Jordan: a multicentric cross-sectional study - Abu-Helalah, Munir; Gharibeh, Tarek; Al-Hanaktah, Mohammad; Khatatbeh, Islam; Batarseh, Fadi; Asfour, Amro; Okkeh, Omar; Dalal, Abdallah; Alhendi, Ahmad; Ababneh, Huthaifa (Frontiers in Public Health, 2025)
BackgroundSeasonal Influenza is a major cause of morbidity and mortality worldwide. Despite the well-established preventive role of the influenza vaccine particularly for patients at high risk, influenza vaccine uptake remains suboptimal. In Jordan, data on the influenza vaccine uptake among adults with chronic diseases at high risk of influenza complications is still lacking.MethodsA cross-sectional study was conducted to assess influenza vaccine knowledge, attitudes, uptake, and barriers among adults with selected chronic disease in Jordan. Data was collected via a structured questionnaire based on the health belief model (HBM). The face-to-face interviews were conducted between February and June 2023 at multiple healthcare centers and hospitals are representative sites of Jordan.ResultsA total of 786 participants completed the study questionnaire with a mean age of 50.04 ± 15.9 years. There was a low uptake rate of influenza vaccine (10.4%) during the 2022/2023 season, while around one third of participants (32.7%) reported history of been ever vaccinated against influenza. This study identified different predictors of influenza vaccine uptake such as advice from the healthcare professional, history of complications from influenza, availability of free influenza vaccine and awareness about the vaccine availability. Worry about the vaccine safety was one of the important detected barriers.ConclusionSimilar to the global trend, particularly in developing countries, the influenza vaccine uptake rate is low among adults with different high-risk illnesses in Jordan. Results of the study provided baseline data for future interventions to improve the uptake rates of influenza vaccines in Jordan.